Design of Blood‐Compatible Interfaces with Poly(vinyl ether)s. Issue 12 (4th May 2016) - Oda, Yukari; Zhang, Cui; Kawaguchi, Daisuke; Matsuno, Hisao; Kanaoka, Shokyoku; Aoshima, Sadahito; Tanaka, Keiji
Abstract : Diblock copoly(vinyl ether)s (PVEs) containing oxyethylene side‐chains with methoxy and ethoxy groups are designed for the construction of a bio‐inert interface. It is successfully demonstrated that the design of the side‐chain structure of PVEs strongly impacts the aggregation state of the polymer as well as the aggregation state of water at the interface, leading to excellent blood‐compatibility.